Evaluation of Tarannum Al-Quran Teaching in Malaysian National Religious Secondary School - Mohd Aderi Che Noh; Farah Ilyani binti Zakaria; Khadijah Abdul Razak; Hafizhah Zulkifli (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2021)
This study aims to examine students' perceptions of the implementation of Tarannum al-Quran teaching in Program Kelas Khas Kemahiran al-Quran (KKQ) from the aspect of the teaching development process in the classroom based on the CIPP Model (Stufflebeam & Shinkfield 1985). Data were obtained through questionnaires and semi-structured interviews. The sample of this study involved 78 from four KKQ students in religious, national secondary schools (SMKA), including boarding schools (SBP) in the state of Selangor from 106 population and three teachers as participants. The validity and reliability of the questionnaire instrument obtain a high value with a correlation score between items exceeding 0.25 in addition to content verification by expert reference panel and an overall alpha value of 0.95. At the same time, the semi-structured interview protocol was also confirmed by experts. Questionnaire data were analyzed descriptively using Statistical Package for Social Sciences (SPSS) 11.5 involving frequency, percentage, mean and standard deviation. At the same time, the interview data were analyzed and transcribed verbatim to identify the elements involved. The findings show that teachers understand and implement the necessary details in the teaching development process, but it is only moderately high. These elements can be seen through various techniques and strategies, taking into account the diversity of students' levels and abilities and the positive reinforcement that always occurs in the interaction of teachers and students. In conclusion, the implementation of teaching at the stage of teaching development is only at a moderately high level with incremental implications that require continuous development and improvement.